Utilization of Bread and Milled Corn Waste to Support Energy Sources of Kacang Goats - P. Padang; H. Harmoko; S. Abdullah; S. W. Cakrawati; M. Mustafa (Jurnal Sain Peternakan Indonesia, 2023)
This study aimed to evaluate the production performance of Kacang goats fed with bread waste and ground corn as an energy source in a concentrated arrangement. The research cattle were 12 female Kacang goats. This study used t-test analysis to compare the two treatments. The results of the t-test analysis showed that bread waste as an energy source increased body weight gain, efficiency in the use of dry matter and crude protein rations, carcass percentage, internal non-carcass percentage, external non-carcass percentage and nonedible carcass percentage compared to goats given ground corn as a source of energy in a concentrated form. However, slaughter weight, dry matter consumption, crude protein consumption, carcass weight, carcass component weight, internal non-carcass weight, external non-carcass weight, and edible non-carcass weight showed no significant difference between the treatments.